Analysis of Regulatory Loopholes in The Broadcasting Law and PSE Regulations on The Distribution of RCTI+ OTT Content - Vanggi Eka Riski (ULTIMA Comm, 2026)
Digital transformation has reshaped Indonesia's media industry through the rapid growth of Over-the-Top (OTT) services, shifting audiences from scheduled broadcasting to on-demand streaming while challenging existing regulatory frameworks. Regulatory overlap between the Broadcasting Law and the Electronic System Operator (PSE) regime has created ambiguity over the authority of the Indonesian Broadcasting Commission (KPI) and the Ministry of Communication and Information Technology. This study examines how RCTI+ exploits these regulatory gaps using Robert W. McChesney's Media Political Economy Theory. Employing a critical paradigm and qualitative case study of Indonesia's broadcasting and PSE regulations, the study finds that RCTI+ strategically shifts between legal regimes to circumvent broadcasting obligations, transforming audiences from citizens into data commodities without public accountability. Rather than representing isolated regulatory inconsistency, these practices reflect structural conditions that enable corporate media power to exploit fragmented digital governance. The findings demonstrate that regulatory classification determines the democratic accountability of digital media, making legal compliance inseparable from communication democracy. These findings also reaffirm the analytical value of McChesney's framework for explaining how regulatory fragmentation facilitates corporate regulatory arbitrage within hybrid media systems in developing countries.